REVISITING THE HISTORY OF TAKAYASU DISEASE: STUDIES AND SURGICAL TREATMENT - Shavkat I. Karimov; Akmal A. Irnazarov; Abdurasul A. Yulbarisov; Khojiakbar K. Alidjanov; Viktoriya E.Tsay; Eldor M. Mirkomilov; Elnora R. Djuraeva (Central Asian Journal of Medicine, 2022)
Nonspecific aortoarteritis (Takayasu disease) is a systemic disease belonging to the group of vasculitis, mainly affecting the arteries of the elastic and muscular-elastic types of large and medium caliber with localization of the inflammatory process in the media and adventitia. The article describes the history of the development of ideas about clinical manifestations, morphological changes and the course of the disease from 1761 to the present, the chronology of medical achievements in the study of this disease.